Digital transformation obstacles categorization in higher education institutions in the middle east and its effect on the UN sustainable development goals: A systematic literature review - El-Bayaa, Nourhan (Edelweiss Applied Science and Technology, 2025)
The operations and curriculum of higher education institutions are undergoing significant changes and challenges in the ME region. These significant changes are being driven by a number of factors and are not allowing this sector to achieve sustainability goals. The Sustainable Development Goals (SDGs) have a strong link to the use of digital transformation, especially in higher education, and those goals could be achieved with the use of digital technologies (SDG 4). Therefore, students use digital tools to enhance their learning, which include a variety of tools chosen to incorporate formalized learning environments in higher education instruction. In this article, we identify those challenges based on a systematic literature review. The study identifies hurdles to digital transformation in higher education in the ME area, including internal and external issues. Furthermore, the paper demonstrates how to employ digital transformation approaches to achieve one of the 17 Sustainable Development Goals set forth by the UN and links the usage of digital transformation in ME area higher education institutions with these goals. The study provides a full understanding of impediments, allowing for effective tactics and solutions. This research article identifies the six main obstacles that face digital transformation in higher education institutions in the Middle East area, then categorizes them into five categories. Furthermore, this article identifies the role of digital transformation in achieving SDG 4, which is the quality of education in HEIs in the ME. Higher education institutions are complex, and in such an area as the Middle East, it is not easy to implement any transformation, especially digital transformation, due to numerous challenges in this area. Based on a systematic literature review, we identify such challenges in this study. The article finds both internal and external barriers to the digital transformation of higher education in the ME region. Additionally, the study ties the use of digital transformation in higher education institutions in the ME area with the 17 Sustainable Development Goals established by the UN and shows how to use digital transformation methodologies to accomplish one of these goals. Effective strategies and solutions are made possible by the study's thorough comprehension of the obstacles.